Electroretinographic detection of human brain dopamine response to oral food stimulation12. (20th June 2013) - Nasser, J.A.; Parigi, A. Del; Merhige, K.; Wolper, C.; Geliebter, A.; Hashim, S.A.
Abstract Objective: The activity of dopamine‐dependent retinal signaling can be assessed using electroretinography. Response of this system to oral food stimulation might provide accessible insight into the brain dopamine response to oral stimuli as retinal dopamine concentration is dependent upon mid brain dopamine concentration was postulated. Design and Methods: Nine individuals had cone ERG (b wave) response to oral food stimulation and oral methylphenidate (MPH) administration measured on separate days, and completed self reported eating behavior questionnaires. Results: Significant and similar increases in b wave response to both stimuli (P = 0.012 and P = 0.042, MPH and food, respectively) and significant correlations of the food stimulated b wave amplitude with binge eating related behavior as measured by the Gormally Binge Eating Scale (r = 0.68, P = 0.044) and self‐reported trait hunger as measured by the Stunkard and Messick Three Factor Eating Questionnaire (r = 0.67, P = 0.048) were found. Conclusion: The significant increase in food stimulated dopamine dependent b wave amplitude and correlation with methylphenidate stimulated b wave amplitude suggest that ERG may offer a relatively inexpensive and accessible methodology for potentially assess dopaminergic responses to food and other externally applied stimuli that have been implicated in the pathogenesis of a number of human diseases.